INVESTIGASI PERSEPSI INTERNATIONAL FINANCIAL REPORTING STANDARDS (Students' Journal of Accounting and Banking, 2014)
This study examined the level of student understanding of International Financial Reporting Standards (IFRS). Financial reporting standards are constantly changing to follow the growing age, where the world globally now use IFRS as its financial reporting standards. Thus the authors examine the extent to which the student has knowledge of IFRS. The study was conducted by examining differences in the knowledge of students by gender, and levels of education. This study used a sample of 349 respondents. The questionnaire contains questions about the shared knowledge of IFRS and IFRS differences with US GAAP. After that, the data is processed using ANOVA Test respondents. As a result, there was no difference in knowledge of IFRS by gender, also found no differences in student knowledge of IFRS education. This study has limitations in that the sample population was taken. Therefore, in subsequent studies suggested expanding area of research. Keywords: IFRS Knowledge, Perception, Sex Education Level